The Thai-Burmese border: drug studies of Plasmodium falciparum in pregnancy. - Mcgready, R; Nosten, F (1999)
Plasmodium falciparum malaria is increasing world-wide, as is resistance to the available antimalarials. On the Thai-Burmese border this problem is most acute in pregnant women, as options for their treatment are even more restricted because of the unknown effects of antimalarials on the foetus. Presented here are the results of descriptive, clinical, drug studies on quinine, mefloquine and artemisinin derivatives for P. falciparum in pregnant women. Mefloquine and quinine have high failure rates for primary and recrudescent infections. Artemisinin-based treatments in pregnant women have proved safe, tolerable and efficacious. However, randomized drug studies with these drugs and other new antimalarials are required to define the true safety and efficacy of these drugs in pregnant women.